1999
DOI: 10.1159/000016942
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function in Compensated Hepatic Cirrhosis: Effects of an Amino Acid Infusion and Relationship with Nitric Acid

Abstract: Aims: In order to assess the possible participation of nitric oxide (NO) in renal function during compensated hepatic cirrhosis, we studied renal function, the plasma and urinary levels of cGMP and the concentration of nitrates and nitrites, as markers of NO synthesis in blood and urine, in 10 patients with Child A hepatic cirrhosis as compared with 10 control subjects, both under basal conditions and during stimulation (amino acid-induced glomerular hyperfiltration). Methods: To study renal function, the glom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Others (Zaman et al, 1999;Choi et al, 2003) found no relation between Doppler parameters and HVPG due to significant variability in portosystemic collateral patterns (Merkel et al, 1998). The significant differences were between groups as to splenic vein diameter, splenic vein cross sectional area, splenic vein mean flow velocity and splenic vein congestion index agreed with others (Rodriquez et al, 1999;El Zeiny et al, 2002;Kayacetin et al, 2004), but differed due to lower sample sizes (De Bem et al, 2006) or due to liver disease with bleeding varices (Choi et al, 2003).…”
Section: Discussionsupporting
confidence: 56%
“…Others (Zaman et al, 1999;Choi et al, 2003) found no relation between Doppler parameters and HVPG due to significant variability in portosystemic collateral patterns (Merkel et al, 1998). The significant differences were between groups as to splenic vein diameter, splenic vein cross sectional area, splenic vein mean flow velocity and splenic vein congestion index agreed with others (Rodriquez et al, 1999;El Zeiny et al, 2002;Kayacetin et al, 2004), but differed due to lower sample sizes (De Bem et al, 2006) or due to liver disease with bleeding varices (Choi et al, 2003).…”
Section: Discussionsupporting
confidence: 56%
“…In hypertensive patients with an activated renin-ANG system, unopposed activity of ANG II was not involved in the L-NAME-induced pressor response and renal vasoconstrictor response, whereas the L-NAME-induced decrease in GFR was enhanced, indicating a greater dependence of GFR on NO-mediated vasodilator tone during sodium depletion ( Van der Linde et al, 2003). In patients with hepatic cirrhosis and portal hypertension, GFR and effective renal plasma flow were lower than in the control subjects, and, under basal conditions, cyclic GMP and NO levels in plasma and urine were higher; the renal plasma flow change was more marked in the patient group and the GFR values were similar in both groups (Rodriquez et al, 1999). It was concluded that the increased cyclic GMP and NO levels in plasma and urine imply a maintained vasodilatory action that may at least partly compensate for the vasoconstrictor effect of ANG II in patients with hepatic cirrhosis and portal hypertension.…”
Section: B Renovascular Responsementioning
confidence: 76%
“…98 Some authors described in patients with liver disease that this state of renal hyperfiltration is accompanied by a lack of response to an amino acid stimulus. 98 This lack of response was not observed in other studies 99,100 in which cirrhotic patients showed a response to amino acid infusion similar to that of controls.…”
Section: Stu Dies In Patien Tsmentioning
confidence: 67%